B1: So sánh
A =[tex]\frac{2006}{2007}-\frac{2007}{2008}+\frac{2008}{2009}-\frac{2009}{2010}[/tex]
B=[tex]-\frac{1}{2006.2007}+\frac{1}{2008.2009}[/tex]
$ A = \frac{2006}{2007} - \frac{2007}{2008} + \frac{2008}{2009} - \frac{2009}{2010} \\ = \left ( 1 - \frac{1}{2007} \right) - \left ( 1 - \frac{1}{2008} \right ) + \left ( 1 - \frac{1}{2009} \right) - \left ( 1 - \frac{1}{2010} \right) \\ = 1 - \frac{1}{2007} - 1 + \frac{1}{2008} + 1 - \frac{1}{2009} - 1 + \frac{1}{2010} \\ = \frac{1}{2008} - \frac{1}{2009} + \left (\frac{1}{2010} - \frac{1}{2007} \right ) \\ = \frac{1}{2008} - \frac{1}{2009} + \left (\frac{-3}{2007 . 2010} \right) \\ = \frac{1}{2008} - \frac{1}{2009} + \left (\frac{-1}{2007 . 670} \right ) $
$ B = - \frac{1}{2006 . 2007} + \frac{1}{2008 . 2009} \\ = \frac{-1}{2006 . 2007} + \frac{1}{2008} - \frac{1}{2009} $
$ 2006 > 670 \\\Leftrightarrow 2006 . 2007 > 670 . 2007 \\\Leftrightarrow \frac{1}{2016 . 2017} < \frac{1}{670 . 2007} \\\Leftrightarrow
\frac{-1}{2016 . 2017} > \frac{-1}{670 . 2007}
\\\Leftrightarrow \frac{-1}{2016 . 2017} + \frac{1}{2008} - \frac{1}{2009} > \frac{-1}{670 . 2007} + \frac{1}{2008} - \frac{1}{2009} \\\Leftrightarrow B > A $